Environmental Accounting from the New Institutional Sociology Theory Lens: Branding or Responsibility? - Ani Wilujeng Suryani; Eka Rofida (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
Drawing on the new institutional sociology theory, this study aims at exploring the implementation of environmental accounting. We analysed sustainability and annual reports of 39 manufacturing companies in Indonesia from 2010 to 2017. The hypotheses of the study were tested using multiple linear regression analysis. The results indicated that company reputation has a positive effect on environmental accounting. However, public ownership has no effect. These results showed that community power failed to encourage companies to disclose environmental accounting. The environmental reporting provided by companies was merely a ceremonial for the good company reputation. The findings of this study contribute to the policy development in which the government might need to tighten regulations for companies to administer their impacts on the environment and provide awards for those succeeding in implementing environmental accounting.